The Mighty Pollinators - Frost, Helen; Lieder, Rick (2024)
"Have you noticed, on a summer's day, the fine powder at the heart of a flower or floating on a breeze? What is pollen, and why does it matter? Almost invisible, pollen waits for the one thing it needs: a ride on the wind-or on wings, fur, or feathers. That's where pollinators come in, small and mighty, holding the world together with their work. Soft, shimmering photographs saturated with color evoke the busy world of bees, butterflies, bats, and moths-and many lesser-known species-at arrestingly close range. Playful poems encourage the reader to look closely, to marvel, and most of all, to care, while concise back matter underscores the vital role these creatures play in the ecosystem and the ways we can help pollinators help us. A seventh seamless blend of poetry, nonfiction, and captivating photography from the dynamic duo behind Step Gently Out, The Mighty Pollinators belongs in every classroom-and in the hands of any curious child eager to understand nature and its wonders"--
Ages 2-5